Large‐Area Bright Emission of Plasmon‐Coupled Dark Excitons at Room Temperature - Hyun Jeong; Hyeong Chan Suh; Ga Hyun Cho; Huitae Joo; Yeonjeong Koo; Hayoung Ko; Ki Kang Kim; Youngbum Kim; Jeongyong Kim; Kyoung‐Duck Park; Mun Seok Jeong (Advanced Science)
Abstract Brightening dark excitons in transition metal dichalcogenide monolayers (MLs) can provide large‐area ultrathin devices for applications in quantum information science and optoelectronics. For practical applications of dark excitons, a robust and bright emission over a wide area at room temperature is desirable; however, no reliable approach has been demonstrated thus far. In this study, an efficient approach is presented for brightening dark excitons at room temperature over a large area of a WSe2 ML via coupling between plasmons and dark excitons. When a WSe2 ML is placed on gold micropillars (Au MPs), dark excitons are efficiently coupled to strongly localized surface plasmons at the edges of the Au MPs, along with a strong photoluminescence (PL) emission. Room‐temperature dark exciton emission is confirmed via energy‐, angle‐, and time‐resolved spectroscopy experiments, as well as confocal PL mapping. This study provides a generalizable method for the practical application of dark exciton.